Elevated Plasma Histone H4 Levels Are an Important Risk Factor in the Development of Septic Cardiomyopathy - Nian-Fang Lu; Li Jiang; Bo Zhu; De-Gang Yang; Rui-Qiang Zheng; Jun Shao; Jing Yuan; Xiu-Ming Xi (Balkan Medical Journal, 2020)

(untitled)
Background:Myocardial impairment is a major complication and an important prognostic predictor of sepsis. Therefore, early and accurate diagnosis as well as timely management of septic cardiomyopathy is critical to achieve favorable outcomes.Aims:To investigate the risk factors of septic cardiomyopathy.Study Design:Cross-sectional study.Methods:This study performed between May 2016 and June 2018 recruited 93 septic patients from the intensive care unit. All patients received standardized treatments. Septic patients were divided into two groups: non cardiomyopathy (n=45) and septic cardiomyopathy group (n=48). Blood samples were collected and transthoracic echocardiography was performed within 24 hours of intensive care unit admission. Septic patients with one ultrasound abnormality but no history of heart disease were diagnosed as having septic cardiomyopathy. Plasma histones, cardiac troponin I, and N-terminal pro-brain natriuretic peptide were measured using ELISA. Sequential Organ Failure Assessment scores, vasopressor use, and the outcomes of intensive care unit stay were analyzed. Spearman rank analysis was used to determine the correlation between plasma histone H4 and other parameters. Binary logistic regression and receiver operating characteristic curve analysis were used to determine the risk factors for septic cardiomyopathy.Results:Compared with the non-cardiomyopathy group, the septic cardiomyopathy group had significantly higher plasma H4 and cardiac troponin I levels, a higher Sequential Organ Failure Assessment score, more frequent vasopressor use, and a higher mortality rate (p<0.05). Plasma histone H4 levels positively correlated with cardiac troponin I (r=0.577, p<0.001), N-terminal pro-brain natriuretic peptide (r=0.349, p=0.001), and Sequential Organ Failure Assessment scores (r=0.469, p<0.001). Binary logistic regression and receiver operating characteristic curve analyses revealed that elevated plasma histone H4 levels and vasopressor use were important risk factors for septic cardiomyopathy (p<0.05).Conclusion:Elevated plasma histone H4 levels could be used to predict septic cardiomyopathy in patients with sepsis.